Case Study: University Lecture Timetabling Without Pre-registration Data - Sze, San Nah; Bong, Chia Lih; Chiew, Kangleng; Tiong, Wei King; Noor Alamshah, Bolhassan (IEEE, 2017)
This paper focuses on university lecture timetabling at Faculty of Computer Science and Information Technology (FCSIT), Universiti Malaysia Sarawak (UNIMAS). In this case study, course pre-registration is not a practice. Therefore, there is no precise estimation on course registration and causes faculty’s experienced planner to arrange the timetable by curriculum-based. However, curriculum-based timetable will create a lot of changes after the semester has started. Besides, students are increasing consistently from semester to semester although the number of venue resources remains the same. Due to all these issues, the objective of this study is to develop a computerised algorithm to minimise the clashes issue and increase venue utilisation. Data pre-processing algorithm was carried out to predict course registration. Then, a two-stage heuristic method is proposed to solve the faculty course timetabling problem by student-based. The simulator was tested with three real semesters’ data from FCSIT. All the timetable solutions generated by the simulator are no-clash solution with minimum unallocated courses. In term of venue utilisation, two-stage heuristic solution manages to allocate exactly with the demand up to 98% but real solution can perform best at only 75%.